PENGARUH LABEL HALAL DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus pada Pelanggan Kosmetik Wardah di Kota Sumbawa ) - Indri Afriliantini; Abdul Salam; Abdurrahman (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2019)
The purpose this study is to determine : 1) Effect of halal labels on wardah cosmetic purchasing decision. 2) Effect of celebrity endorser on purcahasing decisions. The model used in data analysis is the research instrumens, classic assumption test, multiple linear analysis, and test the hypothesis. The analytical tool used in this study is SPSS Data used is primary data and secondary data with sampling purposive sampling. The result of this study show 1) label halal label has a positive and significant what is indicated by the value for the halal label variabel is equal to 0.000 where is this value < 0,5. 2) celebrity endorser have a positive and significant shown by the value for the celebrity endorser variable value is equal to 0.014 where is this value > dari 0,5.